New english second - Jones, Rhodri (Heinemann Educational London, 1978)
New English Second by Rhodri Jones provides comprehensive English language lessons aimed at improving students' grammar, vocabulary, and communication skills. The book is designed to enhance learners' fluency and confidence in both written and spoken English through engaging exercises and activities.